The aesthetics of unity in Kendang Pangarjan performed by I Dewa Nyoman Sura and Cokorda Alit Hendrawan - I Putu Swaryandana Ichi Oka; I Wayan Rai S.; I Wayan Suharta (Journal of Aesthetics, Creativity and Art Management, 2022)
The purpose of this study was to analyze the aesthetics of unity that exist in kendang pangarjan which is performed by two Balinese drummers namely I Dewa Nyoman Sura and Cokorda Alit Hendrawan. Data collection is done by observation, interviews, literature studies, and document studies. The results showed that kendang pangarjan is one type of instrument found in Balinese gamelan. Two names of kendang pangarjan performances whose expertise have been very famous in Bali are I Dewa Nyoman Sura and Cokorda Alit Hendrawan. The aesthetics of unity in question is divided into three elements, namely unity in diversity which includes processing the color of the sound which then forms a song sentence; unity in purpose which includes the function of each. Kendang (lanang/male and wadon/female) instruments are different, but in carrying out their duties they have the same goal, namely as an interpreter of the tempo and dynamics of the song, and; unity in fusion that can be viewed from the philosophy of naming the lanang-wadon (male-female) instrument which in human life reflects the blend of men and women. Keywords: Kendang Pangarjan, unity, male and female drum.